"Occurrence of Clinostomum Complanatum (Rudolphi, 1819) (Digenea: Clinostomatidae) in Capoeta capoeta gracilis (Osteichthys: Cyprinidae) from Shiroud River, Iran" - M Malek; I Mobedi (Tehran University of Medical Sciences, 2001)
112 specimens of Capoeta capoeta gracilis from the Shrioud river were examined. The prevalence and abundance of parasites were significantly higher in the area between the mouth to behind the opercle. Susceptibility of infection was not significantly different between male and female fish. The prevalence of infection was the lowest in the largest length group. Histopathological study revealed blood feeding metacercaria cause myositis.